Analysis of the Deleterious Single-Nucleotide Polymorphisms Associated With Antidepressant Efficacy in Major Depressive Disorder - Xin, Juncai; Yuan, Meng; Peng, Yonglin; Wang, Ju (Frontiers in Psychiatry, 2020)
Major depressive disorder (MDD) is a serious mental disease with negative affects on almost all aspects of the patient. Currently, antidepressants are the major ways to ease or treat MDD. However, the existing antidepressants have limited efficacy in treating MDD, with a large fraction of patients either responding inadequately to antidepressants in the initial therapy, or responding differently to the drugs during the treatment. Pharmacogenetics studies have found that SNPs in some genes are associated with the efficacy of antidepressants. In order to obtain a better understanding on the relationship between the SNPs and antidepressant efficacy, we compiled a list of 233 SNPs significantly associated with the efficacy of antidepressants in MDD. Of the thirteen nonsynonymous SNPs (nsSNPs) in the list, three (rs1065852, rs3810651 and rs117986340) may influence the structures and function of the corresponding proteins. Besides, the influence of rs1065852 on the structure and structural flexibility of CYP2D6 was further investigated via molecular dynamics simulations. The results indicated that the flexibility of the F-G loop for mutant was reduced compared to the native CYP2D6. As a portion of the substrate access channel, this may decrease the approximability of the substrates to the channel. Hence, the lower flexibility of the substrate access channel may lead to the low enzyme activity of mutant, which could help to design the new antidepressants. Our results will help us to understand the impact of genetic variation on efficacy of antidepressants and provide useful information for developing more effective antidepressants.